Tiktok Social Media as a Platform for Promoting a Healthy Lifestyle Through Creative Exercise Videos - Oktariyana; Noviria Sukmawati; Leni Pebriantika (Universitas Negeri Semarang, 2025)
This study aims to explore in depth the use of the social media platform TikTok as a tool for promoting healthy lifestyles through the distribution of creative exercise videos presented in an innovative and captivating way. This study applies a descriptive qualitative method with content analysis techniques, involving 20 creative physical exercise videos on TikTok selected based on their high engagement and viral nature. Data collection was conducted through structured observation, audio-visual recording, and examination of the health messages contained in each video, whether through verbal, non-verbal, or visual elements. The analysis focused on patterns of information delivery, movement aesthetics, music utilization, and user interaction mechanisms. Research findings reveal that creative exercise videos on TikTok have great potential as a means of promoting health. Several factors that increase the effectiveness of the content include: easy and repetitive exercise movements that are simple to follow, dynamic music to boost enthusiasm, short video lengths so as not to tire the viewer, and lively visual elements to evoke emotional appeal. Furthermore, TikTok's interactive features such as comment sections, duets, stitches, and challenges have been proven to encourage user participation in reproducing exercise movements, thereby creating a chain effect that expands the spread of health promotion messages. The results of the study confirm that TikTok is not only an entertainment platform, but also an efficient health communication channel with a visual-learning approach. This digital participation-based health promotion model has the potential as a contemporary strategy to increase public awareness and motivation toward physical activity and the formation of healthy lifestyles. Therefore, TikTok holds strategic value in the development of public health programs during the digital transformation era.